1992
DOI: 10.1002/bbpc.19920961003
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Reactions of Phenylacetylene

Abstract: Chemical Kinetics J Complex Compounds J Elementary Reactions J Shock Waves / ThermodynamicsHydrogcn atom abstraction from phenylacetylene (C6HS-C2H) like its reaction with hydrogen atoms have been studied at elevated temperatures behind reflected shocks. -The unimolecular decomposition of very low initial concentrations (3 -22 ppm) of phenylacetylene was investigated in the temperature range 1600 to 1900 K by monitoring the temporal H-atom production. -For C6HS-C2H + H, the thermal decomposition of very low co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 9 publications
0
33
0
Order By: Relevance
“…25 The present method utilizes the reaction at low [H] 0 where the H atoms are produced from the fast thermal decomposition of C 2 H 5 I. 28,29 The pertinent mechanism is given in Table 1 Figure 1 (closed circles) along with the earlier results from the N 2 O decomposition study. 25 It should be noted that reactions 5 and 6 in Table 1 Table 1) at the highest temperature and [C 2 H 5 I] 0 is less than 5%.…”
Section: Methodsmentioning
confidence: 99%
“…25 The present method utilizes the reaction at low [H] 0 where the H atoms are produced from the fast thermal decomposition of C 2 H 5 I. 28,29 The pertinent mechanism is given in Table 1 Figure 1 (closed circles) along with the earlier results from the N 2 O decomposition study. 25 It should be noted that reactions 5 and 6 in Table 1 Table 1) at the highest temperature and [C 2 H 5 I] 0 is less than 5%.…”
Section: Methodsmentioning
confidence: 99%
“…H-and I-atoms from the ethyl iodide decay was found to be about 1.0 and the above mechanism is suited to describe the H atom formation [4].…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, gas-phase reactions of silicon compounds are of importance for the Chemical Vapor Deposition (CVD) process. Concerning bimolecular SiCl 4 reactions, no experimental study at high temperature has been reported in the literature.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…While rate constants for phenyl Send offprint requests to: R. I. Kaiser, e-mail: kaiser@gold.chem.hawaii.edu radicals reacting with olefins and alkynes range between 10 −12 and 10 −14 cm 3 s −1 at temperatures up to 1100 K and entrance barriers were determined to be 25-43 kJ mol −1 , reaction products are purely speculative (Yu & Lin 1995a;Yu & Lin 1995b;Duncan & Trotman-Dickenson 1962;Fahr & Stein 1989;Herzler & Frank 1992). Obviously, the products of the reaction of phenyl with molecular hydrogen as studied by Lin and coworkers should be benzene and atomic hydrogen (Yu & Lin 1995a), but the problem is more complex if unsaturated hydrocarbons are the reactants.…”
Section: Introductionmentioning
confidence: 99%